ChemInform Abstract: Na3Cd3B(PO4)4: A New Noncentrosymmetric Borophosphate with Zero‐Dimensional Anion Units. Issue 1 (3rd January 2013) - Shi, Yunjing; Pan, Shilie; Dong, Xiaoyu; Wang, Ying; Zhang, Min; Zhang, Fangfang; Zhou, Zhongxiang
Abstract The title compound is synthesized by solid state reaction of Na2CO3, CdO, H3BO3, and NH4H2PO4 in the molar ratio 1.5:3:1:4 (sealed silica tube, 680 °C, 3 d).